The classical idea - Dunlop, Geoff; Silleck, Bayley; WNET (Television station: New York, N. Y.). (West Long Branch, N. J. KULTUR, 1989)
Traces the origins of humanism and immortal classical style to Ancient Greece. Probes Greek art and architecture and studies the Parthenon. Shows how thw genius of Roman engineering and architecture was used to build an empire, while portrait sculptures exalted its rulers.
An Annenberg/CPB project.
VHS.
Host, Michael Wood.
Keywords: Art, Classical; Christian art and symbolims -- Roman Influences